Comparative study of corrosion behavior of AA2014/15 Vol%Al2O3p and AA2009/20 Vol% SiCw - Shamsul Baharin, Jamaludin; Z. Yusoff; Khairel Rafezi, Ahmad (Portuguese Electrochemical Society, 2009)
Link to publisher's homepage at http://www.scielo.oces.mctes.pt/scielo.php/script_sci_serial/lng_en/pid_0872-1904/nrm_iso